Effects of Zataria multiflora Boiss. Essential Oil on Aspergillus flavus - H Gandomi Nasrabadi; A Misaghi; A Akhondzadeh basti; A Khosravi; S Bokaei; A Abbasifar (Institue of Medicinal Plants, ACECR, 2008)
Background: Molds are important spoiler of food material and have potential of mycotoxin production. The adverse side effects of chemical preservatives have caused that research focused on use of naturally occurring compound, especially essential oils (EOs), for inhibition of mold growth. Essential oils are natural compounds containing terpenic mixtures that have antimicrobial and antioxidant properties. Zataria multifloro Boiss., a domestic aromatic plant of Iran, has different effect such as antispasmodic and antibacterial. Objective: In this study effect of Z. multiflora Boiss. Essential oil on growth and spore production by Aspergillus flavus and its morphological alteration action were investigated. Method: After extraction of essential oil with steam distillation method, it was analyzed by GC-MS. Evaluation of essential oil effect on growth and spore production carried out by agar dilution method. For SEM evaluation, mold cultured on PDA was fixed with osmium tetroxide and blocks of agar were coated with gold and observed by scanning electron microscope. Results: Effect of EO on growth and spore production by A. flavus was significant in all concentrations studied. MIC and MFC values were 400 and 1000 ppm, respectively. SEM analysis showed excessive sporulation of mold culture in absence of EO while sporulation of culture containing EO was very sparse. Morphological changes such as irregular surface with many folds and distortion of hyphae were seen in cultures treated with EO. Conclusion: Inhibitory effect of Z. multiflora Boiss. Essential oil demonstrated in this study candidate this EO as a substitution of chemical preservatives.